Estimation of Glomerular Filtration Rate: An Update: Reprinted for our readers interest originally published PJKD 2018;2(4):38-42. - Shafi, Salman Tahir (Pakistan Journal of Kidney Diseases, 2021)
Glomerular filtration rate (GFR) estimation is the fundamental component of assessment of renal function. Kidney disease: Improving global outcomes (KDIGO) guidelines define chronic kidney disease (CKD) as decline in GFR of <60 ml/min/1.73m2 or presence of kidney damage for 3 or more months 1. GFR can be measured indirectly as the clearance of exogenous filtration markers that are eliminated by the kidney only by glomerular filtration i-e Inulin, Iothalamate, Iohexol, 51Cr-EDTA or 99mTC-DTPA. In routine clinical practice, GFR is assessed from serum concentrations of endogenous filtration markers like Urea, creatinine or Cystatin C. This review will discuss the different aspects of estimation of GFR and its implications.